Democracy and terrorism in Africa - Chimere Okechukwu Iheonu; Simplice Asongu; Shedrach A. Agbutun; Innocent A. Ifelunini (African Governance and Development Institute (AGDI), 2021)
This study adds to the body of existing literature on the relationship between democracy and terrorism by investigating the impact of democracy on terrorism in 26 African countries. The study utilises a robust measure of democracy known as the varieties of democracy index which has been observed in literature to be more superior to conventional measures of democracy. A composite index of terrorism was derived from the number of terrorism incidents, the number of terrorist fatalities, and the number of terrorist injuries utilising the principal component analysis. The study utilises a Fixed Effects regression with Driscoll and Kraay standard errors and account for simultaneity utilising the first lags of the regressors as instruments. The result reveals an inverted U-shaped relationship between democracy and terrorism in the selected African countries. In particular, early stages of democracy are associated with higher levels of terrorism while later stages of democracy are associated with lower levels of terrorism. The study provides recommendations based on these findings.
Keywords: 330; Democracy; Terrorism; Africa; Instrumental Variable; Fixed Effects Model